1413. A Phase IIa Efficacy, Safety, Tolerability and Pharmacokinetic (PK) Study of Encochleated Amphotericin B in Patients with Mucocutaneous (Esophogeal, Oropharyngeal, Vulvovaginal) Candidiasis Who are Refractory or Intolerant to Standard Non-Intravenous Therapies. (26th November 2018) - Kibathi, Lilian; Kumar, Parag; Lionakis, Michail; Urban, Amanda; Ferre, Elise; McManus, Maryellen; Colton, Benjamin; Lambros, Chris; Lu, Ruying; Mannino, Raphael; Tramont, Edmund; Freeman, Alexandra F
Abstract: Background: Current oral therapeutic options for chronic mucocutaneous candidiasis (CMC) are often associated with resistance and toxicity. Amphotericin B (AMB) has broad fungicidal activity and markedly resists emergence of resistance but requires parenteral administration and monitoring for significant nephrotoxicity, which worsens with chronic treatment. Encochleated amphotericin B (CAMB) is a novel oral formulation of AMB. In animal models, CAMB demonstrates antifungal activity with similar efficacy as intraperitoneal AMB deoxycholate, but without the associated toxicity. This on-going patient volunteer study assesses the efficacy, safety, tolerability and PK of CAMB in patients with CMC who are refractory or intolerant to standard oral azole antifungals. Methods: Four patients have completed the clinical protocol treatment period: 3 patients with STAT3 deficient Hyper IgE syndrome and CMC, and one patient with chronic esophageal candidiasis. Eligible patients were dose escalated (Figure 1), with option of enrolling in an extension phase. Serial plasma PK samples were collected over 24 hours over the study period, with data available from two patients (Figure 2). Results: CAMB was well tolerated by all four patients, and all are currently on the extension phase (Figure 3). There was significant improvement in clinical severity symptom scores of esophageal and oropharyngeal symptoms; CAMB01 achieved reduction in clinical symptoms by 57% (800 mg/day), CAMB02 by 85% (400 mg/day), CAMB03 50% (800 mg/day) and CAMB04 50% (800 mg/day). CAMB02 maintained higher plasma PK exposure throughout the study compared with CAMB01, a possible explanation for clinical response at a lower 400 mg/day dose. Reported adverse events were grade 1, mostly nausea and dizziness. There were no signs of liver, kidney or hematologic toxicity in any of the patients, with CAMB01 and CAMB02 receiving study drug for 1 year. Conclusion: CAMB was well tolerated in patient volunteers with long-standing symptomatic azole-resistant CMC. All four patients have met the primary endpoint of achieving 3 50% clinical response. CAMB is a promising oral therapy for patients with history of CMC, with potential use in treatment and prophylaxis of invasive fungal infections. Disclosures: M. Lionakis, Matinas BioPharma Inc: Research Support, Research support. R. Lu, Matinas BioPharma Inc: Employee and Shareholder, Salary. R. Mannino, Matinas BioPharma Inc: Employee and Shareholder, Salary.